Strategi Kepemimpinan Kepala Sekolah dalam Meningkatkan Kualitas Lembaga Pendidikan Islam di Pedesaan : Studi MTsN 3 Aceh Jaya, Kecamatan Krueng Sabee - Nurma Dewi (Lembaga Studi Agama dan Masyarakat Aceh (LSAMA), 2025)
This article explores the leadership strategies of the head of MTsN 3 Aceh Jaya in enhancing the quality of Islamic education in rural areas. Facing challenges related to access to educational resources and the impacts of globalization, the head of the madrasah plays a vital role in establishing a strong external network. By collaborating with the government, teacher organizations, and the community, as well as ensuring transparency in financial management, the madrasah can bolster support from the local community. Improving teacher competencies and engaging alumni are also key priorities in the effort to enhance educational quality. Interviews reveal that a collaborative and participatory approach not only enriches the teaching and learning process but also fosters a sense of ownership among community members. Overall, active and responsive leadership is essential for overcoming challenges and achieving success in Islamic education in rural settings.